Digital Professions and the Future of Zakat: A Maqāṣid-Based Study of the 2024 Fatwa by the Indonesian Ulema Council (MUI) - Ryan Bianda; Muhammad Yosef Niteh; Maad Ahmad; Aang Gunaepi (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2025)
The rise of digital professions in Indonesia, particularly YouTubers and social media influencers, has challenged conventional frameworks of Islamic jurisprudence on zakat. To address this normative gap, the Majelis Ulama Indonesia (MUI) issued Fatwa 2024, which mandates zakat on income earned through digital platforms. This study aims to critically examine the manhaj istinbāṭ (legal reasoning methodology) employed in the fatwa, focusing on its integration of ushul al-fiqh principles and maqāṣid al-sharī‘ah values. Using a qualitative content analysis approach, the study evaluates primary texts, classical fiqh sources, and socio-economic data. The fatwa demonstrates a hybrid reasoning model combining qiyās, maslahah mursalah, and contextual deliberation, reclassifying digital income under zakatable categories. It also affirms that only lawful income is eligible for zakat, excluding unethical earnings such as those from hoaxes or immoral content. Findings reveal that while the fatwa offers strong theological and epistemic foundations, its practical implementation faces challenges, including low awareness among digital workers and fragmented institutional support. Nevertheless, the fatwa represents a forward-looking articulation of Islamic law that is responsive to modernity while remaining grounded in tradition. This research contributes to Islamic legal studies by offering a detailed analysis of how fatwas evolve in response to digital economic realities, and proposes strategic directions for enhancing fatwa efficacy and digital zakat governance.